Mapping and Evaluating Marine Protected Areas and Ecosystem Services: A Transdisciplinary Delphi Forecasting Process Framework - Belgrano, Andrea; Novaglio, Camilla; Svedäng, Henrik; Villasante, Sebastián; Melián, Carlos J.; Blenckner, Thorsten; Bergström, Ulf; Bryhn, Andreas; Bergström, Lena; Bartolino, Valerio; Sköld, Mattias; Tomczak, Maciej; et al. (Frontiers in Ecology and Evolution, 2021)
In this perspective, we present a transdisciplinary approach based on the Delphi method forecasting process framework, for mapping and evaluating Marine Protected Areas (MPAs) for their ability to protect biodiversity while providing Ecosystem Services (ES) and related human well-being benefits – i.e., the ecosystem outputs from which people benefit, including, for example, fish production and carbon sequestration. We highlight the need to include the human dimensions of marine protection in such assessments, given that their effectiveness over time is conditional on the social, cultural, and institutional contexts in which they evolve. In support of an Ecosystem-Based Management (EBM), we propose an overall approach to explore and map biodiversity and ES components in MPAs and their linkages to human well-being. We also highlight the importance of MPAs to support objectives for restoration, conservation, and sustainable development in relation to EU Directives such as the Marine Strategy Framework Directive (MSFD), the Maritime Spatial Planning Directive (MSPD), and the Common Fisheries Policy (CFP).